Photopatternable and Rewritable Epoxy‐Anhydride Vitrimers. Issue 2 (22nd January 2021) - Giebler, Michael; Alabiso, Walter; Wieser, Viktoria; Radl, Simone; Schlögl, Sandra
Abstract : Back Cover : In article number 2000466 by Sandra Schlögl and co‐workers, the introduction of photolabile o‐nitrobenzyl ester chromophores endows epoxy‐anhydride vitrimers with spatially controlled solubility properties. Positive‐tone microstructures are inscribed by photolithography and the patterns are thermally erased via catalyzed transesterifications.